Development of novel O-polysaccharide based glycoconjugates for immunization against glanders - Burtnick, Mary N.; Heiss, Christian; Schuler, A. Michele; Azadi, Parastoo; Brett, Paul J. (Frontiers in Cellular and Infection Microbiology, 2012)
Burkholderia mallei, the etiologic agent of glanders, causes severe disease in humans and animals and is a potential agent of biological warfare and terrorism. Diagnosis and treatment of glanders can be challenging, and in the absence of chemotherapeutic intervention, acute human disease is invariably fatal. At present, there are no human or veterinary vaccines available for immunization against disease. One of the goals of our research, therefore, is to identify and characterize protective antigens expressed by B. mallei and use them to develop efficacious glanders vaccine candidates. Previous studies have demonstrated that the O-polysaccharide (OPS) expressed by B. mallei is both a virulence factor and a protective antigen. Recently, we demonstrated that Burkholderia thailandensis, a closely related but non-pathogenic species, can be genetically manipulated to express OPS antigens that are recognized by B. mallei OPS-specific monoclonal antibodies. As a result, these antigens have become important components of the various OPS-based subunit vaccines that we are currently developing in our laboratory. In this study, we describe a method for isolating B. mallei-like OPS antigens from B. thailandensis oacA mutants. Utilizing these purified OPS antigens, we also describe a simple procedure for coupling the polysaccharides to protein carriers such as cationized bovine serum albumin, diphtheria toxin mutant CRM197 and cholera toxin B subunit. Additionally, we demonstrate that high titer IgG responses against purified B. mallei LPS can be generated by immunizing mice with the resulting constructs. Collectively, these approaches provide a rational starting point for the development of novel OPS-based glycoconjugates for immunization against glanders.